Titanium Alloys for Biomedical Implants and Devices - Attar, Hooyar; Kent, Damon (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This special issue provides a current snapshot of recent advances and ongoing challenges in the development of titanium alloys for biomedical implants and devices. Titanium offers significant advantages over other materials including higher strength and better biocompatibility. This issue highlights current trends and recent developments, including the uptake of additive manufacturing (3D printing), and approaches to improve processing and performance of titanium alloys for medical applications.